2022
DOI: 10.3389/fnint.2022.821109
|View full text |Cite|
|
Sign up to set email alerts
|

Cerebellar Volumes and Sensorimotor Behavior in Autism Spectrum Disorder

Abstract: BackgroundSensorimotor issues are common in autism spectrum disorder (ASD), though their neural bases are not well understood. The cerebellum is vital to sensorimotor control and reduced cerebellar volumes in ASD have been documented. Our study examined the extent to which cerebellar volumes are associated with multiple sensorimotor behaviors in ASD.Materials and MethodsFifty-eight participants with ASD and 34 typically developing (TD) controls (8–30 years) completed a structural MRI scan and precision grip te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 105 publications
(169 reference statements)
3
4
0
Order By: Relevance
“…6A ). This corroborates findings of hypoplasia in posterior vermal and lobular regions, which have been reported consistently before in clinical samples 46 48 , 50 , 51 . While the functional parcellation also reveals smaller volumes throughout almost all ROIs, with significant differences in MDTB components 1) Left-hand presses and 6) Divided attention (right), the MDTB components 7) Narrative and 8) Word comprehension seem to not follow the same trend (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…6A ). This corroborates findings of hypoplasia in posterior vermal and lobular regions, which have been reported consistently before in clinical samples 46 48 , 50 , 51 . While the functional parcellation also reveals smaller volumes throughout almost all ROIs, with significant differences in MDTB components 1) Left-hand presses and 6) Divided attention (right), the MDTB components 7) Narrative and 8) Word comprehension seem to not follow the same trend (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Lidstone et al (2021) showed aberrant connectivity between the cerebellum and cerebral cortex in 105 children with ASD and found that elevated RRBs were associated with low right posterior cerebellum-left inferior parietal lobule connectivity and high right posterior cerebellar-right connectivity. A recent study of McKinney et al (2022) reported a relationship between the clinical score of RRB and the white matter volume of the right cerebellar consistent with the well-known role of the cerebellum in the modulation of cognitive and social functions; interestingly, such areas control also eye fixation and pursuit movements (Shemesh & Zee, 2019).…”
Section: Discussionsupporting
confidence: 63%
“…Intriguing reports from mouse models show that targeted activation of right Crus I and the posterior vermis was able to rescue autistic behaviors in TSC1 mutant mice by modulating activity in the medial prefrontal cortex (Kelly et al, 2020). Akin volumetric changes in Crus I and the posterior vermis have been reported in human studies as well as deviations in total cerebellar size (Courchesne et al, 2001;D'Mello et al, 2015;Kaufmann et al, 2003;McKinney et al, 2022;Stanfield et al, 2008). Recently, however, no differences in cerebellar anatomy in individuals with autistic traits were reported when using normative models on cerebellar growth based on a smaller control sample (N=219) (Laidi et al, 2022).…”
Section: Discussionmentioning
confidence: 93%